2019
DOI: 10.1108/idd-09-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Applying empathy-driven participatory research methods to higher education new degree development

Abstract:  Purpose: Innovation and entrepreneurship are economic drivers promoting competition and growth among organizations throughout the world, many of which would not exist without well-established new product development processes coupled with intentional and strategic focus on research and development. New product development processes, such as the lean start-up methodology and design thinking, are well-known and thriving as a result of empirically-grounded research efforts. Unfortunately, educational institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The study found that learning preference was one of the main predictors of coding achievement and computational thinking skills. Bosman et al (2019) have shown one approach to how students can be used within the new program development process. The study used participatory research, wherein students act as researchers and actively participate in the data collection and analysis process.…”
Section: The Interaction Between Learning Preference and Other Factors In A Learning Contextmentioning
confidence: 99%
“…The study found that learning preference was one of the main predictors of coding achievement and computational thinking skills. Bosman et al (2019) have shown one approach to how students can be used within the new program development process. The study used participatory research, wherein students act as researchers and actively participate in the data collection and analysis process.…”
Section: The Interaction Between Learning Preference and Other Factors In A Learning Contextmentioning
confidence: 99%
“…The motive of education institutions is to equip the future generation for upcoming challenges (e.g., social, economic, legal). Unfortunately, even in this era, most of academia are lacking the resources and skills to chase and tackle the modern challenges (Cao and Zhou., 2018;Bosman et al, 2019). Due to these obstacles, academia in developing countries is not obliged in full capacity to help their citizens.…”
Section: Individual Csr's Dimension On the Basis Of Regional Educatiomentioning
confidence: 99%
“…However, at present, educational institutions in other countries seem lagging when it comes to resource-based new program/degree development processes (Bosman et al, 2019;Giacomarra et al, 2019) and there are several weaknesses and limitations in the expansion of innovation and entrepreneurship education in colleges and universities characterized by too much theoretical teaching than practical activities (Cao and Zhou, 2018). Lombardi and other scholars carry out a two-way comparison between Italy and Singapore to investigate how these countries conceive and implement an entrepreneurial culture just highlighting Singaporean is one of the leading national investor in entrepreneurial education (Lombardi et al, 2017).…”
Section: Ebr 323mentioning
confidence: 99%
“…Results show Jordan entrepreneurship education is still at an early stage of development with very few courses dealing with small business and entrepreneurship topics. Bosman et al (2019) implement participatory research by means of photovoice, photo-elicitation and focus groups that involve students for collecting qualitative data. Students worth the following key-attributes: learning style (agency and choice, active hands-on learning and real-world applications) and learning context (technology and design- Internal university stakeholders focused assignments, integration of humanities and self-selected disciplines of interest) (Bosman et al, 2019).…”
Section: Ebr 323mentioning
confidence: 99%
See 1 more Smart Citation